Relapse rates in patients with rheumatoid arthritis in stable remission tapering or stopping antirheumatic therapy: interim results from the prospective randomised controlled RETRO study. Issue 1 (6th February 2015) - Haschka, Judith; Englbrecht, Matthias; Hueber, Axel J; Manger, Bernhard; Kleyer, Arnd; Reiser, Michaela; Finzel, Stephanie; Tony, Hans-Peter; Kleinert, Stefan; Feuchtenberger, Martin; Fleck, Martin; Manger, Karin; et al.
Abstract : Objective: To prospectively analyse the risk for disease relapses in patients with rheumatoid arthritis (RA) in sustained remission, either continuing, tapering or stopping disease-modifying antirheumatic drugs (DMARDs) in a prospective randomised controlled trial. Methods: Reduction of Therapy in patients with Rheumatoid arthritis in Ongoing remission is a multicentre, randomised controlled, parallel-group phase 3 trial evaluating the effects of tapering and stopping all conventional and/or biological DMARDs in patients with RA in stable remission. Patients (disease activity score 28 (DAS28)<2.6 for least 6 months) were randomised into three arms, either continuing DMARDs (arm 1), tapering DMARDs by 50% (arm 2) or stopping DMARDs after 6 months tapering (arm 3). The primary endpoint was sustained remission during 12 months. Results: In this interim analysis, the first 101 patients who completed the study were analysed. At baseline, all patients fulfilled DAS28 remission and 70% also American College of Rheumatology- European League Against Rheumatism Boolean remission. 82.2% of the patients received methotrexate, 40.6% biological DMARDs and 9.9% other DMARDs. Overall, 67 patients (66.3%) remained in remission for 12 months, whereas 34 patients (33.7%) relapsed. The incidence of relapses was related to study arms (p=0.007; arm 1: 15.8%; arm 2: 38.9%; arm 3: 51.9%). Multivariate logistic regression identified anticitrullinated protein antibodies (ACPA) positivity (p=0.038) and treatment reduction (in comparison to continuation) as predictors for relapse (arm 2: p=0.012; arm 3: p=0.003). Conclusions: This randomised controlled study testing three different treatment strategies in patients with RA in sustained remission demonstrated that more than half of the patients maintain in remission after tapering or stopping conventional and biological DMARD treatment. Relapses occurred particularly in the first 6 months after treatment reduction and were associated with the presence of ACPA. Trial registration number: 2009-015740-42.